Detection of ampicillin based on the fluorescence of a biocatalytic oxidation product - García-Zamora, José Luis; Alonso-Arenas, Jessica; Rebollar-Pérez, Georgette; Pacheco-Aguirre, Francisco M.; García-Diaz, Esmeralda; Torres, Eduardo (Frontiers in Environmental Science, 2022)
Antibiotics used in humans and farmed animals are an essential source of water and soil contamination. Ampicillin is a micropollutant commonly found in water, sludge, food, flora, and fauna. However, the methods used for its detection in environmental samples are often complicated and expensive. Therefore, developing more straightforward strategies to detect well-known target antibiotics is necessary. In this context, enzyme-based detection methods have been demonstrated to be selective, sensitive, rapid, and relatively simple. In this study, a fluorescent byproduct from the ampicillin oxidation using Chloroperoxidase (CPO) enzyme was used as a pointer compound to determine ampicillin concentration in environmental water samples. We oxidized 80% ampicillin for 1h, producing a fluorescent compound with m/z 274.2517. A response surface methodology (RSM) based on a central composite design (CCD) was used to evaluate and optimize the effects of hydrogen peroxide, enzyme concentration, and time as independent variables on the maximum fluorescence signal as the response function. The methodology proposes to build a calibration curve that relates the initial concentration of ampicillin with fluorescence intensity after the reaction with CPO, which helps detect ampicillin in the concentration range from 0.035 to 40 μM, with a limit of detection of 0.026 μM. The application of the method to fortified environmental water samples allowed percentages of recovery from 86 to 140%. The formation of the fluorescent compound was not affected by the presence of salts commonly found in wastewater; however, it was affected by other antibiotics. The proposed methodology was tested in the context of water from water bodies, urban, and WWTP effluents.